1993
DOI: 10.1002/1097-0142(19930615)71:12<3868::aid-cncr2820711213>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of undetected intrapulmonary metastases in resected lung cancer

Abstract: Background. Between 1975 and 1989, 839 patients with lung cancer underwent pulmonary resection at Okayama University Medical School; for this study data of the 42 (5.0%) who had intrapulmonary metastasis were analyzed. Results. The 5‐year survival rate for the 42 patients was 25.7%, which was significantly better than that of patients with Stage IV disease and extrapulmonary metastasis, none of whom survived for 3 years. The 2‐year survival rate was found to be significantly better in patients with one‐lobe me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…Regional recurrence may be caused by intrapulmonary metastasis in segments other than the Table 4 for details b Patients in the compromised group did not undergo systemic lymph node dissection specimen segment(s) in the same lobe, by regional lymph node metastasis, or by an incomplete resection margin. The incidence of regional lymph node metastasis and intrapulmonary metastasis in the same lobe has been reported to be 2% and 10%, respectively, in cases of stage I NSCLC [1,9,17,19,20,23]. In our own series of pathologic investigations of 101 stage I NSCLC patients who underwent lobectomy, intrapulmonary metastasis in the resected lobe was found in 2% of patients and mediastinal or lobar lymph node metastasis was found in 10.9%.…”
Section: Discussionmentioning
confidence: 77%
“…Regional recurrence may be caused by intrapulmonary metastasis in segments other than the Table 4 for details b Patients in the compromised group did not undergo systemic lymph node dissection specimen segment(s) in the same lobe, by regional lymph node metastasis, or by an incomplete resection margin. The incidence of regional lymph node metastasis and intrapulmonary metastasis in the same lobe has been reported to be 2% and 10%, respectively, in cases of stage I NSCLC [1,9,17,19,20,23]. In our own series of pathologic investigations of 101 stage I NSCLC patients who underwent lobectomy, intrapulmonary metastasis in the resected lobe was found in 2% of patients and mediastinal or lobar lymph node metastasis was found in 10.9%.…”
Section: Discussionmentioning
confidence: 77%
“…PM have been reported to account from as low as 3% to as high as 10% of all surgically treated patients with NSCLC [14][15][16] and the prevalence among surgical series partly depends upon how carefully the pathologists look for them, as well as upon the prevalence of bronchioloalveolar carcinoma which, in its multifocal form, may mimic the presence of PM and may influence the survival results because of its known favourable prognosis. Our study excluded patients with pure BAC, thus avoiding possible misinterpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 27 of the 28 malignant lung tumors (96%) associated with multiple focal pure GGOs were adenocarcinomas. Shimizu et al [20] reported that a subgroup of patients with lung cancer associated with intrapulmonary metastasis have a good prognosis, especially when the disease is diagnosed T1N0 at pathologic examination. Nakajima et al [21] also reported that such a subgroup exists among patients with intrapulmonary metastasis.…”
Section: Ground-glass Opacities In Ct Of Lung Cancermentioning
confidence: 99%